Cognitive Behaviour and Relaxation Techniques: A Comparative Study among University Students in Nigeria with Primary Insomnia - , Victor Moses; , Balarabe Musa; , Mohammed Indo Aisha; , Umaru Yunusa (Archives of Current Research International, 2018)
The purpose of the study was to examine the comparative effectiveness of cognitive behavior and relaxation techniques among undergraduate students in Nigeria with primary insomnia. A non-randomized design involving pretest and posttest was used. A total sample of thirty-six undergraduate students with a mean age of 25.5, who were identified with primary insomnia condition were purposively selected and assigned to treatment and control group. The treatment administered lasted for six weeks. Insomnia Severity Index was used as the outcome measure and was administered at pre and post intervention stages to assess treatment outcome. The data collected was analyzed at the .05 significance level using SPSS ver. 24. After adjusting for the covariate, the results suggest statistically significant differential effects for groups, F(2,30) = 16.775, p < .001, η2 = .512, with cognitive behavior technique (CBT) producing higher within group remission of averagely 65% compared to 45% for relaxation technique (RT) and 9% for control (CTL). Sleep onset time for CBT and RT groups reduced from a within group average of 39.1 to 21.2 minutes and 40.8 to 19.5 minutes while total sleep time improves from 5.0 to 6.4 and 4.2 to 6.6hrs respectively. Sleep efficiency for CBT improves from 70 to 86% in contrast to 71 to 85% for RT. The study concluded that both interventions (CBT and RT) were effective but comparatively, CBT appears as a viable option and could be recommended as a first first-line behavioral intervention for psychologists and counsellors to explore it benefits to help students manage sleep difficulty in school.